Evaluasi Kinerja Lalu Lintas Terhadap Kapasitas Ruas Jalan Di Kota Bandung (Studi Kasus: Jalan Raya Ujung Berung Kota Bandung) - Rivaldi, Ryan; Novriani, Shinta (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2024)
Bandung City, as the capital of West Java Province, is also the largest metropolitan city in the region. As a center for local and regional trade, education, tourism, culture and industry, Bandung has developed rapidly. The Ja lan Ujung Berung section in Ba ndung City is an important access to the city center, often traversed by motorized vehicles. This research aims to evaluate the performance of Jalan Ujung Berung in Bandung City. The research method uses the guidelines of the Indonesian Road Capacity Manual (MKJI 1997) by conducting direct surveys in the field. Utilizing Microsoft Excel, calculations of capacity, velocity, side resistance, volume, degree of saturation, and level of service (Los) were generated from the processed data. The survey findings spanning four days revealed the following: a maximum volume of 23,598.25 PCU/hour, an average speed of 27.68 kilometers per hour, and a saturation degree of 0.85. It is feasible to conclude that Jalan Ujung Berung offers service at level D, according to the findings of the analysis.